Psychological Impact of Rising Lifestyle Diseases: Awareness and Coping Strategies - Gaurav, Urvashi; Sharma, Priyanka; Dadhich, Meenakshi; Saloni, Saloni; Vats, Rahul; Mehta, Rashi (Journal of Neonatal Surgery, 2025)
This study tries to understand the psychological impact of rising lifestyle diseases on senior secondary students in Delhi, focusing on their awareness and coping strategies. As lifestyle-related health issues such as obesity, hypertension, diabetes, and mental health problems become more prevalent, their psychological effects on students—especially those in the critical 12th standard year—are increasingly concerning. The research was conducted with 14 students from two government schools, Sarvodaya Kanya Vidyalaya (SKV) and Sarvodaya Bal Vidyalaya (SBV) in East District, Delhi, with a balanced representation of 8 male and 6 female participants. Through both qualitative and quantitative data, the study highlights that while the students are generally aware of lifestyle diseases, they have limited understanding of their long-term consequences. The psychological effects reported by the students include stress, anxiety, and issues related to body image, which are compounded by the physical and emotional strain of these diseases. Coping mechanisms such as exercise, dietary changes, and mindfulness practices were found to be common strategies students use to manage the challenges. This research emphasizes the need for a more comprehensive approach to health education in schools, one that raises awareness about lifestyle diseases and equips students with effective tools to manage their mental and emotional well-being.